Microglia-mediated neuroinflammation and neuroplasticity after stroke - Wang, Yuan; Leak, Rehana K.; Cao, Guodong (Frontiers in Cellular Neuroscience, 2022)
Stroke remains a major cause of long-term disability and mortality worldwide. The immune system plays an important role in determining the condition of the brain following stroke. As the resident innate immune cells of the central nervous system, microglia are the primary responders in a defense network covering the entire brain parenchyma, and exert various functions depending on dynamic communications with neurons, astrocytes, and other neighboring cells under both physiological or pathological conditions. Microglia activation and polarization is crucial for brain damage and repair following ischemic stroke, and is considered a double-edged sword for neurological recovery. Microglia can exist in pro-inflammatory states and promote secondary brain damage, but they can also secrete anti-inflammatory cytokines and neurotrophic factors and facilitate recovery following stroke. In this review, we focus on the role and mechanisms of microglia-mediated neuroinflammation and neuroplasticity after ischemia and relevant potential microglia-based interventions for stroke therapy.